A Neonate with an Unusual Midline Defect and Cardiovascular Anomaly - Poryo, Martin; Hoffmann, Paul; Schäfers, Hans-Joachim; Meier, Clemens-Magnus; Altmeyer, Katrin; Abdul-Khaliq, Hashim; Zemlin, Michael; Meyer, Sascha (European Journal of Pediatric Surgery Reports, 2018)
We present a female neonate with a sternal cleft (SC) and additional aortic aneurysm who presented with respiratory failure. Stabilization of the SC was achieved by using the xyphoid process as an autologous graft bridging the upper part of the SC. We conclude that a step-wise correction of the SC with the use of an autologous graft may improve respiratory function, and should be considered when complete surgical correction is not feasible.
Keywords: aortic aneurysm; sternal cleft; surgical repair